Kristy and the haunted mansion - Martin, Ann M.; Copyright Paperback Collection (Library of Congress) (New York ; Toronto : Scholastic, 1993)
Kristy and her all-star softball team have trouble returning home from a game and end up at a mansion which looks haunted. Will Kristy and the team survive a night in a spook house?
"An Apple paperback."
Keywords: Babysitters; Clubs; Babysitters; Clubs